1812 : Napoleon in Moscow. - Austen, Paul Britten (Pen and Sword, 2012)
At the gates of Moscow, Napoleon's Grand Army prepares to enter in triumphal procession. But what it finds is a city abandoned by its inhabitants - save only the men who emerge to fan the flames as incendiary fuses hidden throughout the empty buildings of Moscow set the city alight. For three days Moscow burned, while looters dodged the fires to plunder and pillage. And so begins 1812: Napoleon in Moscow, Paul Britten Austin's atmospheric second volume in his acclaimed trilogy on Napoleon's catastrophic invasion of Russia. After the fires died down the army settled in the ruins of Moscow; for f.